Cuidado de enfermería desde la perspectiva del paciente con VIH/SIDA - Minchola Pinglo, Isabel Cristina (2016)
Descriptive qualitative research, it aimed to describe and analyze the care provided by nurse from the perspective of the patient with HIV/AIDS. Boff (1999) and Waldow (2006) were the authors who provided the theoretical support of the study. The methodological approach with descriptive method, the dynamic depth interviews and participant observation was developed in seven games with seven participants. For data analysis, use was made of the principles of discourse analysis. The results of the thesis were based on dialogue between researchers and participants through the process of analysis, synthesis and categorization, emerged the categories Visibility care and (In) visibility of care. The first care visibility with 5 themes: 1) friendly care, with love, affection and interest; 2) Spiritual care; 3) instrumental and expressive activity; 4) Educational Care; 5) Biosecurity. The second, (in) visibility of care with 5 themes: 1) Body Care delegated by the nurse; 2) Body Care with (in) sensitivity and authoritarianism; 3) (Dis) interest in the person; 4) Discrimination, fear of contagion and disrespect; 5) Lack of communication and lack of contact. The study findings revealed the patient's perspective with HIV/AIDS on nursing care.